Long distance dispersal of a rescued wolf from the northern Apennines to the western Alps. - CIUCCI, Paolo; MAIORANO, Luigi; BOITANI, Luigi; REGGIONI W (Journal of Wildlife Management, 2009)
By using Global Positioning System technology, we documented the long-distance dispersal of a wolf (Canis lupus) from the northern Apennines in Italy to the western Alps in France. This is the first report of long-distance dispersal of wolves in the human-dominated landscapes of southern Europe, providing conclusive evidence that the expanding wolf population in the Alps originates from the Apennine source population through natural recolonization. By crossing 4 major 4-lane highways, agricultural areas, and several regional and provincial jurisdictions, the dispersal trajectory of wolf M15 revealed a single, narrow linkage connecting the Apennine and the Alpine wolf populations. This connectivity should be ensured to allow a moderate gene flow between the 2 populations and counteract potential bottleneck effects and reduced genetic variability of the Alpine wolf population. The case we report provides an example of how hard data can be effective in mitigating public controversies originating from the natural expansion and recolonization processes of large carnivore populations. In addition, by highlighting the connectivity between these 2 transboundary wolf populations, we suggest that documenting long-distance dispersal is particularly critical to support population-based, transboundary management programs.